A pessoa com deficiência e o direito ao trabalho - Laraia, Maria Ivone Fortunato (2009)
The master s degree dissertation demonstrates the person with deficiency path in the search of the recognition of his rights, focusing the protection foreseen in several international diplomas destined to the reconstruction of the human values, in the the Federal Constitution of 1988 and in several infraconstitutional laws. It defines the person with deficiency in our juridical system, enlarging the list of the Ordinances ns. 3.298/1999 and 5.296/2004, based in the international legal system and in the jurisprudence. The development of the concepts of human dignity, equality and non discrimination are the foundations for the creation of affirmative actions, seeking to the social inclusion of the persons with deficiency, and they are object of a fast approach. In Brazil, the equalization of access opportunities to the job market for persons with deficiency is looked for through the adoption of a system of quotas or legal reserve. The Brazilian system of quotas forces to the persons with deficiency recruiting in the formal market of work, through contract between employee and employer, or through the use of reserved vacancy in public contest. The compulsory nature of person with deficiency recruiting, the increase of the fiscalization by the Labor Department and by the Labor Public Prosecution Service and the recruitings without any planning are cause of legal and social questions. To guarantee the economical function of the companies and to motivate the Brazilian system of quotas, this work proposes the adoption of fiscal and social security measures, the creation of subsidies and the alteration of the Law n. 8.742/93, in order to increase the forecast of a temporary suspension of the payment of the benefit of the special attendance when of the beginning of a labor activity of any species, until the person with deficiency returns to the inactivity. The person with deficiency social inclusion is accompanied of a series of important subjects, treated by the work, that should be faced by the State and by the whole society